The surface impacts of Arctic stratospheric ozone anomalies - K L Smith; L M Polvani (Environmental Research Letters, 2014)
In the Arctic stratosphere, total column ozone in the spring can vary, from year to year, by as much as 30%. This large interannual variability, however, is absent from many present-generation climate models, in which the prescribed seasonal cycle of stratospheric ozone includes, at best, smooth multi-decadal trends. We here investigate the extent to which interannual variability in Arctic stratospheric ozone is able to affect the surface climate of the Northern Hemisphere extratropics. We do this by contrasting pairs of model integrations with positive and negative springtime ozone anomalies, using a simple yet widely used climate model. For ozone anomaly amplitudes somewhat larger than the recent observed variability, we find a significant influence on the tropospheric circulation, and the surface temperatures and precipitation patterns. More interestingly, these impacts have very clear regional patterns—they are largest over the North Atlantic sector—even though the prescribed ozone anomalies are zonally symmetric. However, confirming other studies, for ozone anomaly amplitudes within the observed range of the last three decades, our model experiments do not show statistically significant impacts at the surface.